In Search of Islamic Constitutionalism (American Journal of Islam and Society, 2004)
This article examines the question of whether the Shari`ah is compatible with the principle and procedural form of western constitutionalism. The article will answer this question by looking at the arguments put forth by opponents of Islamic constitutional law and various counter-aguments. Using the substantive approach, I assert that the Shari`ah is compatible with constitutionalism. This position rejects both the fundamentalists’ and the secularists’ views on this subject. The Shari`ah’s principles can be a formal source or an inspiration to a constitution.